Organophosphonic acid and cerium functionalized antimonotungstate with electrochemical promise in biosensing bacterial dissimilatory sulfite reductase gene sequence. (13th February 2023) - Tang, Zhigang; Zhang, Wenshu; Hu, Yalun; Jia, Xiaodan; Meng, Lina; Wang, Dan; Chen, Lijuan; Zhao, Junwei
Abstract : An organophosphonic acid and cerium functionalized antimonotungstate was reported, and its application in the electrochemical biosensing of the bacterial dissimilatory sulfite reductase gene sequence was explored. Abstract : The rational design and synthesis of organically functionalized cluster-based materials has always been a hot topic. Polyoxometalates (POMs) have become primary candidates for fabricating novel organic–inorganic hybrid cluster-based materials owing to their multiple coordination sites and modes, unique electronic configurations and variable constituents. Herein, an unprecedented organophosphonic acid and cerium functionalized antimonotungstate [H2 N(CH3 )2 ]9 Na12 H6 [Ce3 (H2 O)2 W8 (Hgps)2 O20 ][B-α-SbW9 O33 ]4 ·66H2 O (1, H5 gps = glyphosine) was synthesized in CH3 COOH–CH3 COONa buffer solution. Its tetrameric polyanion [Ce3 (H2 O)2 W8 (Hgps)2 O20 ][SbW9 O33 ]4 27− consists of four Keggin [B-α-SbW9 O33 ] 9− (SbW9 ) segments linked by a dumbbell-shaped [Ce3 (H2 O)2 W8 (Hgps)2 O20 ] 9+ core. Furthermore, we prepared a ternary composite material (denoted as Au-rGO-1 ) containing 1, reduced graphene oxide (rGO) and Au nanoparticles, which exhibits remarkable electrical conductivity and long-term stability. Subsequently, Au-rGO-1 was applied as an electrode modification material to construct an electrochemical DNA biosensor (EDB) for detecting the bacterial dissimilatory sulfite reductase (DSR) gene from sulfate-reducing bacteria, and the MB/dsDNA/Au-rGO-1 /GCE EDB shows outstanding sensitivity, selectivity and anti-interference capability for detecting the DSR DNA sequence. This research provides an accessible strategy for synthesizing organophosphonic acid and lanthanide functionalized POMs and also demonstrates the great potential of POM-based materials in the application of detecting the DSR gene sequence.